2014
DOI: 10.1017/nws.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional homophily in friendship networks

Abstract: Homophily – the tendency for individuals to associate with similar others – is one of the most persistent findings in social network analysis. Its importance is established along the lines of a multitude of sociologically relevant dimensions, e.g. sex, ethnicity and social class. Existing research, however, mostly focuses on one dimension at a time. But people are inherently multidimensional, have many attributes and are members of multiple groups. In this article, we explore such multidimensionality further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 46 publications
9
106
0
2
Order By: Relevance
“…This prediction is consistent with research on cognitive categorization, which has shown that similarity on multiple dimensions, rather than just a single dimension, is a critical variable influencing whether managers perceive another organization as part of their firm's peer group (e.g., Lant and Baum 1995 equivalents constitute an especially influential reference group also dovetails with the general sociological observation that social actors tend to interact with, and are most likely to be influenced by, other actors who are like themselves along multiple dimensions (see Moody 2001, Block andGrund 2014). Consider, for example, the situation of Bank of America in 2006, the last year in our empirical observation period.…”
Section: Institutional Equivalencementioning
confidence: 99%
“…This prediction is consistent with research on cognitive categorization, which has shown that similarity on multiple dimensions, rather than just a single dimension, is a critical variable influencing whether managers perceive another organization as part of their firm's peer group (e.g., Lant and Baum 1995 equivalents constitute an especially influential reference group also dovetails with the general sociological observation that social actors tend to interact with, and are most likely to be influenced by, other actors who are like themselves along multiple dimensions (see Moody 2001, Block andGrund 2014). Consider, for example, the situation of Bank of America in 2006, the last year in our empirical observation period.…”
Section: Institutional Equivalencementioning
confidence: 99%
“…While initiating and maintaining friendship ties generally requires costs in the form of investment in time and effort, interactions with similar others lower these transaction costs and are more rewarding (Block and Grund, 2014;Völker et al, 2008: 327). For example, same-ethnic peers are more likely to share similar experiences, attitudes, and values.…”
Section: Ethnic Homophily In Low-and High-cost Situationsmentioning
confidence: 99%
“…In contrast to 9 Excluding ego and alter effects for the different ethnic groups may bias the estimate of the respective dyadic effect (see Goodreau et al, 2009;Wimmer and Lewis, 2010). Many studies that focus on ethnic groups exclude these effects due to convergence issues resulting from including the necessarily large amount of additional model parameters (e.g., Block and Grund, 2014;Stark and Flache, 2012). Technically, in our case, including ego and alter effects for all ethnic groups (except the reference category) did not result in major convergence issues.…”
Section: Analytical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, empirical studies confirm that friendships and other close relationships tend to form based on racial homophily (McPherson, Smith-Lovin, and Cook 2001). In a school context, several studies find that students from similar racial backgrounds are more likely to befriend each other (e.g., Moody 2001;Block and Grund 2014;Leszczensky and Pink 2015;Smith et al 2016). Boda and Néray (2015) also show that classifications of each other are more important for social ties than self-classifications: individuals choose friends based on how they classify each other, not how others classify themselves.…”
Section: Friendship Contextmentioning
confidence: 98%